PENGARUH HARGA DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA AGYA DI NASMOCO KALIGAWE SEMARANG - Aditya Cahya Nugraha; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2020)
Nasmoco Kaligawe Semarang is one of Toyota's official dealers in Indonesia with a marketing area in the city of Semarang, which until now has been competing with other car dealers. Toyota Agya is one of the products with the type of LCGC (Low Cost Green Car) motorized vehicle marketed by Nasmoco Kaligawe in the city of Semarang which is in demand by many groups. But there are problems in the sale of Toyota Agya at Nasmoco Kaligawe Semarang in the period of 2017 to 2018, sales declined. This is due to the price and sales promotion of the company which is still less than the maximum compared to competitors. This study aims to determine how the influence of price and sales promotion on Toyota Agya car purchasing decisions at Nasmoco Kaligawe Semarang. The type of research used is explanatory research, where data collection techniques used are using questionnaire and sample as many as 100 people by using purposive sampling technique. Selected respondents were consumers who made a purchase decision for a Toyota Agya car at Nasmoco Kaligawe Semarang. The methodology used to analyze primary data in this study is the validity test, reliability test, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, and significance tests (t and f test) with SPSS version 22. The results showed that there was a significant effect between price on purchasing decisions of 19.2%. Sales promotion has a significant effect on purchasing decisions by 20.7%. Meanwhile, simultaneous price and sales promotion significantly influence purchasing decisions by 25.3% while the rest is influenced by other factors besides price and sales promotion. This means that the better the price and sales promotion, the higher the purchase decision of a Toyota Agya car in Nasmoco Kaligawe Semarang. In addition, sales promotions have an influence with the greatest regression coefficient value, 0.411. Based on the results of the study, researchers can provide suggestions for companies to increase sales promotions to increase public interest in products and provide prices in accordance with the value of the products offered by the company